Kriteria Penentu Kunjungan Wisatawan pada Objek Wisata Alam di Kabupaten Balangan - Hayati, Laila; Siregar, Syarituah (PPJP ULM, 2021)
This research aims to (1) Knowing the most dominant criteria that influence tourists visiting natural attractions in the Balangan Regency, (2) Knowing the choice of natural attractions most likely to be visited by tourists in the Balangan Regency. This research uses descriptive quantitative research, and the research location is in Balangan Regency. In the analysis technique using the AHP (Analytical Hierarchy Process) method based on the results of the calculation, it is obtained from the 4 most dominant criteria in determining visiting tourists, namely natural beauty and the choice of natural attractions that tourists tend to visit from 3 alternative criteria is Mount Hauk.